Utility-scale wind turbines and wind farms - Vasel-Be-Hagh, Ahmad; Ting, David S-K (IET energy engineering series, 2021)
Wind power is a pillar of low emission energy systems. Many recent advances have been achieved in multiple aspects of utility-scale wind power. This structured review conveys recent progress involving aerodynamics, layout, control, environmental concerns, forecasting and intermittency, combination with PV and offshore farms.